Avaliação do efeito do (-)-α-bisabolol em parâmetros de estresse oxidativo em camundongos submetidos ao tratamento agudo com etanol absoluto - Oliveira, Gersilene Valente de (2011)
The (-)-α-bisabolol, at doses of 100 and 200 mg / kg, is an alcohol commonly obtained from Matricaria chamomilla and species of the genus (Vanillosmopsis), it was tested in ethanol-induced gastric injury model for research gastroprotective effect microscopically of this drug, the influence of neutrophil migration in this effect, as well as THE involvement of superoxide dismutase (SOD) and catalase (Cat) enzymes. It was also quantified the lipid peroxidation (Thiobarbituric Acid Reactive Substances-TBARS), and the nitric oxide metabolism product (NO), the anion nitrite. The (-)-α-bisabolol was able to decrease ethanol-induced gastric damage, parameter microscopically analyzed. The (-)-α-bisabolol decreased neutrophils migration to the gastric mucosa in absolute ethanol-induced ulcer model in mice, quantified by the myeloperoxidase enzyme (MPO), present in neutrophils. The (-)-α-bisabolol interacted with the anti-oxidant enzyme system decreasing the catalase enzyme activity in the gastric mucosa in animals treated with absolut ethanol, decreased lipid peroxidation (TBARS) in gastric tissue in rats exposed to ethanol and it was able to increase the superoxide dismutase activity in the same tissue. The (-)-α-bisabolol did not significantly alter the amount of nitrite in the ulcerated animals stomach. Thus, the (-)-α-bisabolol in the doses tested reduced the gastric lesions associated with administration of ethanol, probably by reducing oxidative stress in the stomach while reducing the activity of MPO, it being explained the gastroprotective action of this drug, however the reduction of enzymatic activity of Catalase would be a less important finding to explain the antiulcer activity observed it.